Belonging to the nation : inclusion and exclusion in the Polish-German borderlands, 1939-1951 - Kulczycki, John J., 1941- 1941- (Harvard Univ. Press, 2016)
"In 1939 Nazi Germany incorporated western Poland into the Reich and recognized Germans with Polish citizenship as Volksdeutsche. Following Germany's defeat in 1945, communist-dominated Poland incorporated eastern Germany, recognized German citizens of Polish origin as members of the Polish nation, and established a procedure for Volksdeutsche to rejoin the nation. My study focuses on the processes by which both states sought to nationalize these inhabitants of the transnational Polish-German borderlands that in the imaginations of German and Polish nationalists rightfully belonged to their nation. The process of inclusion and exclusion that accompanies the formation of an imagined national community is often marginalized in discussions of the emergence of nations. My goal is to illustrate the complexity of the process, the obstacles it confronts in practice, and the resulting injustices."...Provided by publisher